Effects of genipin concentration on cross-linked β-casein micelles as nanocarrier of naringenin: Colloidal properties, structural characterization and controlled release. (November 2020) - Li, Mo; Wang, Kunli; Wang, Yuxiao; Han, Qianyun; Ni, Yuanying; Wen, Xin
Abstract: β-casein (β-CN), an amphiphilic protein from bovine milk, has attracted increasingly interest as biocompatible, non-toxic nanocarrier in foods due to its ability to form micellar nanostructures through self-assembling. In this study, the formation of genipin-crosslinked β-casein micelles (G-CNMs) was investigated for the delivery of naringenin, a hydrophobic flavonoid abundant in grapefruits. Our results showed that the degree of micellar crosslinking was dependent on the genipin concentration, as indicated by SDS-PAGE and GPC-MALLS. At the suitable genipin concentration (β-CN/genipin molar ratio of 1:20), the G-CNMs showed intra-micellar crosslinking with average hydrodynamic radius (9.35 nm) as measured by dynamic light scattering. We found that the degree of crosslinking has a significant influence on the aspects of stability and controlled release. G-CNMs overcame destabilization of micelles induced by acid pH (pH = 2) when β-CN/genipin molar ratio was 1:15 or 1:20, while the stability against the high NaCl concentration was not influenced. Specifically, as compared to untreated CNMs, all types of G-CNMs in phosphate buffered saline buffer (10 mM, pH 7.4) revealed slower releases of naringenin. With the increase of genipin amount, the controlled drug release properties was enhanced. Such findings appear to be promising for future applications of β-CN as controlled release nanocarrier for hydrophobic functional ingredient, whose characteristics can be modulated by tailored genipin crosslinking. Graphical abstract: Image 1 Highlights: The formation of genipin-crosslinked β-casein micelles (G-CNMs) was reported for the delivery of hydrophobic flavonoid. Depending on genipin concentration, the monodisperse G-CNMs could be stably formed by intra-micellar crosslinking. G-CNMs can overcome destabilization of micelles induced by acid pH (pH = 2) in proper genipin concentration range. The naringenin release profiles in PBS buffer (pH 7.4) revealed slower release rate after crosslinking of CNMs by genipin.